Conference report: Third International Conference on Climate Services - Lustig, A.; Gawthrop, E; Vaughan, Catherine; Tepley-Ferguson, D; Muñoz, A.G.; Armstrong, K (2014)
The International Conference on Climate Services is the annual meeting of the Climate Services Partnership. This meeting was held in conjunction with the Meteorological Service of Jamaica and the Jamaican Ministry of Water, Land, Environment, and Climate Change; it was generously sponsored by the CGIAR research program on Climate Change, Agriculture, and Food Security, the United States Agency for International Development, and the United Stated National Oceanic and Atmospheric Administration.